Кадровий потенціал підприємств системи споживчої кооперації України: формування та використання - Дробиш, Л. В. (НТУ "ХПІ", 2010)
У статті розглядаються проблеми формування та використання кадрового потенціалу підприємств системи споживчої кооперації України як одного із важелів забезпечення їх конкурентоспроможності у ринкових умовах господарювання. Виявлено основні причини низької якості людських ресурсів та їх вплив на ефективність використання кадрового потенціалу підприємств. Запропоновано шляхи підвищення ефективності використання кадрового потенціалу підприємств системи споживчої кооперації України, що слугуватиме зміцненню їх конкурентних позицій на ринку товарів та послуг.

The article is dedicated to the problems of forming and deployment of human resources in organizations of the system of consumer cooperatives in Ukraine, because human resources play an important role in the achieving of the required competitive position of these organizations in the modern market conditions. The main reasons of the low quality of labour forces are determined by the author, their influence on the deployment effectiveness of human resources in organizations is shown in this article too. The possible ways of the deployment effectiveness increase of human resources in organizations of the system of consumer cooperatives in Ukraine are suggested by the author, the practical use of these proposals can improve the competitive positions of these organizations at the market of goods and services.
Keywords: висококваліфіковані фахівці; конкурентоспроможність; плинність кадрів; ротація кадрів